Early Buddhism Perspective in Vietnam - Nguyen, Duong Van (Journal of Dhamma for Life, 2021)
The academic article was objectives to study on early Buddhism perspective in Vietnam. That is history of Buddhism in Vietnam with elements of (1) Buddhism Exhortation in Vietnam, (2) Journey of Buddhism from India to Vietnam, and (3) The Early Attributes of Buddhism in Vietnam. The interaction between Most Venerable Dam Thien and Emperor Wen of Sui (Yang Jian) about Buddhism in Giao Chau (the name given to Vietnam during the Chinese occupation) was cited by Thong Bien when he spoke with Empress Dowager Y Lan to draw the conclusion that it dates to the second century A.D. in the history of Vietnamese Buddhism. That was unique of interpretative the Buddha teaching with folk life of Vietnamese.